Technical performance evaluation of voltage regulation equipment in a low voltage network (Comparative study) - خيربك, رند; فيصل شعبان,; تمام حيدر , (Latakia University Journal -Engineering Sciences Series, 2023)
This paper presents a technical comparison study between many devices and strategies used to process the issue of voltage regulation in a real local distribution low voltage – network in order to choose the best technical solution. Reference studies presented various and different solutions and proposed many devices and strategies to process this issue, but have not provided any technical comparison between these devices and solutions. In this paper, many of devices for the voltage regulation were used in a part of 0.4 kV network in the city of Lattakia which are: Zig-Zag transformer, D-STATCOM device and automatic voltage regulator. Different operation cases were studied. The methods and devices were evaluated based on technical standards: voltage unbalance, voltage drop, and losses. Results showed the efficiency of the three devices in principle to process the presented problems with variation in performance according on the studied case.